Intrauterine Surgery For Spina Bifida: First Reported Case In Peru - Ventura-Laveriano, Walter (2017)
We report the first successful case of fetal surgery for spina bifida repair in Peru. A pregnant woman was referred to our center at 23 weeks of gestation because of prenatal diagnosis of spina bifida. A multidisciplinary team was formed with the goal of performing the first open intrauterine surgery in Peru. A successful intrauterine surgery was carried out at 25 weeks of gestation and a healthy infant was born by cesarean section at 37 weeks of gestation. We demonstrated the feasibility of this complex intrauterine surgery in our local setting.